Direct Immunofluorescence Using Non-Lesional Buccal Mucosa in Mucous Membrane Pemphigoid - Kamaguchi, Mayumi; Iwata, Hiroaki; Ujiie, Inkin; Ujiie, Hideyuki; Sato, Jun; Kitagawa, Yoshimasa; Shimizu, Hiroshi (Frontiers in Medicine, 2018)
Mucous membrane pemphigoid (MMP) is a rare organ-specific autoimmune subepithelial blistering disease with predominantly mucosal erosions, most frequently affecting the gingiva. Erosions in the oral cavity usually result in markedly decreased quality of life. The major autoantigens are BP180 and laminin332, which are components of basement membrane proteins in the skin and mucosa. Diagnosis is usually difficult due to histological destruction of the tissue and low autoantibody titers. In this study, we evaluated the diagnostic value of direct immunofluorescence (DIF) using non-lesional buccal mucosa in seven cases of MMP. In all seven patients, gingival lesions were clinically observed, and in one of the seven patients, buccal lesions were also clinically observed. First, we performed DIF to detect tissue-bound autoantibodies and complement. DIF from non-lesional buccal mucosa revealed linear deposits of IgG and C3 at the basement membrane zone in all cases. To detect autoantibodies, indirect immunofluorescence (IIF), BP180-NC16A ELISA and immunoblotting were performed. Surprisingly, circulating autoantibodies were unable to be detected in any of the cases by ELISA, IIF, or immunoblotting. Furthermore, histological separation was observed in one patient. In conclusion, DIF using non-lesional buccal mucosa was found to be superior to histological and serological tests for diagnosing mucous membrane pemphigoid. The procedure is technically easy and has high diagnostic value.